2010 2nd International Congress on Engineering Education 2010
DOI: 10.1109/iceed.2010.5940796
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating VHDL in teaching combinational logic circuit

Abstract: Digital System Fundamentals is an elementary course offered by the Faculty of Electrical Engineering in Universiti Teknologi MARA (UiTM) for semester 1 undergraduate students of the Electrical Engineering programs specializing in computer, electronics, communication and instrumentation. As this course is focusing more on designing circuit rather than only knowing the theoretical part of the circuit, students are introduced with a tool which is widely used in the industry known as Very High Speed Integrated Cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In (Abidin et al, 2010), authors describe how the VHDL can be incorporated into the course of digital logic to reinforce the student's theoretical concepts. This should target undergraduate students majoring in electrical engineering in general and computer, electronics, communication, as well as instrumentation, in particular.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In (Abidin et al, 2010), authors describe how the VHDL can be incorporated into the course of digital logic to reinforce the student's theoretical concepts. This should target undergraduate students majoring in electrical engineering in general and computer, electronics, communication, as well as instrumentation, in particular.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Each student had to minimize eight functions (named F 1 to F 8 ), whereas the index in the function name corresponds to its difficulty level. These functions are 1) F 1 = Σm(0, 3) + Σd(1, 2) 2) F 2 = Σm(0, 1, 2, 3, 13, 14) + Σd (12,15) 3) F 3 = Σm(0, 1, 2, 3) + Σd(9, 11) 4) F 4 = Σm(4, 5, 14, 15) + Σd(7, 13) 5) F 5 = Σm(4, 5, 7, 13, 14) + Σd(9, 11, 15) 6) F 6 = Σm(0, 1, 2, 7, 8, 9, 13) + Σd(10, 11) 7) F 7 = Σm(0, 2, 5, 10, 12, 15) + Σd(8, 13) 8) F 8 = Σm(0, 2, 10, 12, 13, 15) + Σd (5,8) The 25 students of Group A had to minimize these functions manually. The 24 students of Group B used DLD-VISU to do the same.…”
Section: Difficulty Levelmentioning
confidence: 99%
“…Several papers can be found that focus on DLD course construction [1]- [3], the usage of commercial tools and hardware description languages (HDL) for learning DLD [4], [5], and employing programmable logic to enhance the effectiveness of DLD learning process [6], [7]. Using HDL and commercial design tools as learning technologies is very useful.…”
Section: Introductionmentioning
confidence: 99%